Effectiveness of amitriptyline for treating functional dyspepsia in adolescents - Indra Mustawa (Paediatrica Indonesiana, 2017)
Background Functional dyspepsia is common among adolescents. Pain reduces children’s quality of life, psychosocial functioning, and school attendance. Amitriptyline is assumed to be one of the alternative treatments in functional dyspepsia.